Flutter foundation with Firebase and Provider. (Packt Publishing, 2022)
Build a solid foundation in Flutter and become an intermediate developer About This Video Build a solid foundation in Flutter and become an intermediate developer Build a complete real-world cross platform app for both iOS and Android Learn about Firebase Auth for Authentication and Firebase Cloud Firestore for the database In Detail Most beginner courses only teach you the individual parts of a framework but don't cover how they all come together to create a real-world application. In this course, we will cover the fundamentals of flutter and dart to construct a solid foundation, as well as learn how to build out the iOS Reminders app's complete layout. Improve our app's navigation by learning how to move between screens and pass data. We'll learn how to structure our code and how to describe our data using classes in Dart; add email authentication to the app using Firebase Auth; our project will utilize the Firebase Firestore as a real-time database; create a custom light and dark theme for the app that the user can choose between and manage the app's overall status using the Provider Package (recommended by Google). By the end of this course, you will be an intermediate Flutter developer. Audience Anyone wishing to begin with Flutter is encouraged to take this course, as it requires no prior programming knowledge.